Naming Pottery in Melikan Village, Klaten Regency: An Anthropolinguistic Study - Kasitasari, Widita Dwi; Suswandi, Irwan (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
Melikan pottery is an intangible cultural heritage that serves not only as a usable object but also embodies aesthetic, historical and social values. Each craft product usually has a name. Names play a crucial role in socio-cultural identity because they can reflect the community’s perspective on its environment. This study examines the naming of pottery in Melikan Village, Klaten Regency, an area renowned for its pottery craft center in Klaten Regency, Central Java. The purpose of this study is to describe the types of naming and meaning of pottery in Melikan Village, Klaten Regency. This type of research is descriptive and qualitative, utilizing data collection methods that include listening and speaking techniques, followed by advanced methods such as recording, note-taking and participant observation. The research data sources were obtained from interviews with informants who have a deep understanding of pottery naming and direct involvement in the pottery-making process. In analyzing the data, this study draws on theories from van Langendonck (2007) and Hough (2016). This research produces conclusions in the form of categorizing pottery in Melikan Village, Klaten, Central Java, into three main categories: the environmental category (9 data), the socio-cultural category (4 data), and the creativity category (4 data).